3(x-4)+2(3x-1)=-3(-3x+1)+2

Simple and best practice solution for 3(x-4)+2(3x-1)=-3(-3x+1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)+2(3x-1)=-3(-3x+1)+2 equation:


Simplifying
3(x + -4) + 2(3x + -1) = -3(-3x + 1) + 2

Reorder the terms:
3(-4 + x) + 2(3x + -1) = -3(-3x + 1) + 2
(-4 * 3 + x * 3) + 2(3x + -1) = -3(-3x + 1) + 2
(-12 + 3x) + 2(3x + -1) = -3(-3x + 1) + 2

Reorder the terms:
-12 + 3x + 2(-1 + 3x) = -3(-3x + 1) + 2
-12 + 3x + (-1 * 2 + 3x * 2) = -3(-3x + 1) + 2
-12 + 3x + (-2 + 6x) = -3(-3x + 1) + 2

Reorder the terms:
-12 + -2 + 3x + 6x = -3(-3x + 1) + 2

Combine like terms: -12 + -2 = -14
-14 + 3x + 6x = -3(-3x + 1) + 2

Combine like terms: 3x + 6x = 9x
-14 + 9x = -3(-3x + 1) + 2

Reorder the terms:
-14 + 9x = -3(1 + -3x) + 2
-14 + 9x = (1 * -3 + -3x * -3) + 2
-14 + 9x = (-3 + 9x) + 2

Reorder the terms:
-14 + 9x = -3 + 2 + 9x

Combine like terms: -3 + 2 = -1
-14 + 9x = -1 + 9x

Add '-9x' to each side of the equation.
-14 + 9x + -9x = -1 + 9x + -9x

Combine like terms: 9x + -9x = 0
-14 + 0 = -1 + 9x + -9x
-14 = -1 + 9x + -9x

Combine like terms: 9x + -9x = 0
-14 = -1 + 0
-14 = -1

Solving
-14 = -1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6(2-4a)=-60 | | 10y+9-6y+2= | | 4x^2-38x+88=140 | | 5n^2+10n^3= | | 6(3x+5)=5 | | 160q=-q^2+8000 | | 5p^2+10pq^2+pq+2q^3= | | 6(x-8)=2x-20 | | 12a^2+32a+140=0 | | x+x+(x+12)+(x+12)=34 | | x^2+9=04 | | 4m^2+2m-11=0 | | 16m^2+160m+400=8 | | 6k^2-40k-14=0 | | -9u-6=-4(u+4) | | x/2-2x/16=3/6 | | 7+5x=159 | | 8x^2-56x+48=0 | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)x(1/7) | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)X1/7 | | -7(w-3)=-5w+27 | | 3/10=-4/1-1/5 | | 0.14=4/80 | | 1-3x-x^3=2x+1 | | -y=-6x+7 | | 10y+36-38y-47= | | 6.673-(-8.29)=-1.617 | | -6a^7+3a^4-a= | | -20/21*21 | | 17x=0.0005 | | 1/2m=7/8 | | 3.1x^2+x^2=4.9x^2 |

Equations solver categories